Identificação de áreas com risco de inundações em Oriximiná-PA: contribuições à elaboração do zoneamento ambiental municipal - FERREIRA FILHO, David Figueiredo (2022)
The flooding event is the one that most affects people worldwide and has been increasing considerably in Brazil and that should be thought along with other environmental variables in the regularization process of environmentally rugged areas. Thus, this research analyzed the application and relaxation of Law No. 13,465/2017 that deals with Land Regularization (REURB), giving a focus on issues in areas environmentally vulnerable to flooding. Para isso, foi selecionado o município de Oriximiná no estado do Pará, utilizando a metodologia de algebra de mapas para identificar áreas suscetíveis a inundações e confrontar com o processo de expansão urbana. As presented results, both the concept of risk society and environmental justice, support the idea that risks are produced by growth and unbridled economic development, which result in consequences and negative impacts for society, becoming evident the trend of legalization of occupations in environmentally vulnerable areas and the possible lack of understanding of the risks produced by those involved, even by the difficulty of qualification and quantification of risks and impacts produced.